ANALISIS DAMPAK INTEGRASI TEKNOLOGI DALAM PEMBELAJARAN DIFERENSIASI - Siti Nur Rohmah; Eka Hendi Andriansyah (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
The diversity of students is a challenge for educators to manage effective learning to produce maximum learning outcomes. Learning outcomes are important to research because they are a measure of success in the learning process. Differentiated learning with technology is one learning strategy that can be applied in the classroom to optimize learning outcomes. Technology integration helps educators implement differentiated learning to meet student characteristics. The aim of this research is to determine the impact of using technology in differentiated learning on student learning outcomes. The research method is a systematic literature review. The articles used are articles in English and Indonesian sourced from Sinta, Google Scholar, ERIC, and Scopus, which were published from 2018 to 2023. The results of the analysis show that previous studies have shown that the use of technology in differentiated learning has a positive impact on academic learning outcomes and the development of students' attitudes. These results show a significant influence at the junior and senior high school levels but do not show optimal results at the elementary school level. Thus, technological assistance can help teachers implement differentiation learning, that is, differentiation of content, processes, and products, in order to improve learning outcomes.Â Keywords: Differentiated Learning, Learning Outcome, Technology